Ultrasound stimulated production of exopolysaccharide with anti-UV radiation activity by increasing cell permeability of Paenibacillus polymyxa. (March 2023) - Li, Zhi-Qiang; Huang, Yi-Lun; Zhang, Jing; Mi, De; Zhou, Wen-Wen
Abstract: Exopolysaccharide (EPS) produced by Paenibacillus polymyxa PYQ1 may be a promising agent used in the cosmetic field for skin care because of its protective benefits against short-wave ultraviolet (UVC, 100–280 nm) radiation, which induces cytotoxicity in HaCaT cells. We attempted to use low-intensity ultrasound to enhance its fermentation, and the yield of EPS increased by 24 % under the optimum ultrasonic treatment (90 W, 45 s in 9 h). Results of further experiments show that low-intensity ultrasound will kill a few bacterial cells. Therefore, the remaining bacterial cells have more space and more nutrients, growing faster and producing EPS more efficiently. The recoverable physical damage caused by ultrasound increased the cell permeability, and for the first time, we found that low-intensity ultrasound up-regulated the expression of membrane transporters involved with the transport of sucrose and polysaccharides. Owing to these changes, the utilization of carbon sources was accelerated, and the transport of EPS was promoted to the outside of bacterial cells such that the production of EPS was enhanced. Graphical Abstract: ga1 Highlights: The production of exopolysaccharide increased by 24 % under the ultrasonic treatment. A few amounts of bacterial cells died rapidly but the rest cells grew faster. Ultrasound increased the cell permeability to enhance the utilization of nutrients. Ultrasound up-regulated the mRNA level of membrane transporters of sucrose.